'Beauty and the beast' in infection: How immune–endocrine interactions regulate systemic metabolism in the context of infection. Issue 7 (27th May 2019) - Wensveen, Felix M.; Šestan, Marko; Turk Wensveen, Tamara; Polić, Bojan
Abstract: The immune and endocrine systems ensure two vital functions in the body. The immune system protects us from lethal pathogens, whereas the endocrine system ensures proper metabolic function of peripheral organs by regulating systemic homeostasis. These two systems were long thought to operate independently. The immune system uses cytokines and immune receptors, whereas the endocrine system uses hormones to regulate metabolism. However, recent findings show that the immune and endocrine systems closely interact, especially regarding regulation of glucose metabolism. In response to pathogen encounter, cytokines modify responsiveness of peripheral organs to endocrine signals, resulting in altered levels of blood hormones such as insulin, which promotes the ability of the body to fight infection. Here we provide an overview of recent literature describing various mechanisms, which the immune system utilizes to modify endocrine regulation of systemic metabolism. Moreover, we will describe how these immune–endocrine interactions derail in the context of obesity. From a clinical perspective we will elaborate how infection and obesity aggravate the development of metabolic diseases such as diabetes mellitus type 2 in humans. In summary, this review provides a comprehensive overview of immune‐induced changes in systemic metabolism following infection, with a focus on regulation of glucose metabolism. Abstract : The immune and endocrine systems ensure two distinct vital functions in the body: protection against infection and maintenance of systemic homeostasis. The endocrine and immune systems closely interact both in absence and in the presence of infection to ensure the most efficient nutrient usage, whilst optimizing the immunological response. Obesity results in dysregulated endocrine control of systemic metabolism. During infection, aberrant interactions between the immune and endocrine systems therefore results both in reduced capacity to fight infection and aggravated metabolic disease.